ANALISIS PENGARUH INPUT PELATIHAN TERHADAP PEMBELAJARAN DAN GENERALISASI: STUDI KASUS PELATIHAN MANAJEMEN KEUANGAN PENGUSAHA KECIL - Hariyatie, Nira (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
The achievement of trainees in transferring the knowledge and skill developed during training in their job is an important factor to measure the success of training. The objective of research was to examine how the training input, trainee characteristics, training design, and work environment were important factors in determining the success of trainee learning process. Furthermore, the result shows that the traineeâs characteristics, training design, and work environment are the significant factor in influencing trainee in applying their knowledge and skill gained at training to their job.